Hybrid cooling system with cryocooler and liquid-nitrogen for HTS-SQUID system. (June 2020) - Hato, Tsunehiro; Tsukamoto, Akira; Adachi, Seiji; Tanabe, Keiichi
Abstract: We developed a hybrid cooling system consisting of a liquid-nitrogen Dewar and a cryocooler with the aim of cooling HTS-SQUIDs fast at operation sites, extending cooling period time, and avoiding noise increase caused by the cryocooler. Liquid nitrogen is evaporated mainly by thermal inflow into the Dewar. Thus, we tried reducing the thermal inflow into a glass Dewar by cooling its inner surface using a small Stirling cryocooler with a cooling capacity of 16 W at 77 K, and examined the cooling period and the operation procedure. We successfully kept 0.6 liter of liquid nitrogen for one week with 0.2 liter reduction. It was also indicated that long time and low noise operation of HTS-SQUIDs would be possible in the hybrid cooling system by temporarily stopping the cryocooler during measurements.